7 Exploring healthcare professionals' attitudes to future care planning with older adults in hospital: qualitative research co-design through multi-professional patient and carer involvement. Issue 3 (1st September 2018) - Bielinska, Anna-Maria; Archer, Stephanie; Urch, Catherine; Darzi, Ara
Abstract : Introduction: Despite evidence that advance care planning in older hospital inpatients improves the quality of end-of-life care (Detering 2010) future care planning (FCP) with older adults remains to be normalised in hospital culture. It is therefore crucial to understand the attitudes of healthcare professionals to FCP in older patients in the hospital setting. Co-design with patients carers and healthcare professionals can generate more detailed meaningful data through better conversations. Aims: To co-design a semi-structured interview (SSI) topic guide to explore healthcare professionals' attitudes to FCP with older adults in hospital. Methods: A multi-professional research group including a panel of patient and carer representatives co-designed an in-depth topic guide for a SSI exploring healthcare professionals' attitudes to FCP with older adults in hospital. Results: The co-designed topic guide encourages participants to explore personal and system-level factors that may influence attitudes to FCP and practice in hospital amongst healthcare staff. Co-designed topics for inclusion in the SSI schedule include: Potential differences between specialist and generalist approaches to FCP The influence of perceived hierarchy and emergency–decision making ability in professionals on FCP discussions The relevance to transitions of care Attitudes to FCP beyond the biomedical paradigm including perceived well–being and psychosocial aspects of care Digital FCP tools including patient–led FCP. Conclusion: Co-designing qualitative research with older people and multi-disciplinary professionals may narrow translational gaps in implementing FCP by setting joint research priorities. Data generated from a co-designed study may expand understanding of hospital-based anticipatory decision-making with older adults. Reference: . Detering KM, Hancock AD, Reade MC, Silvester W. The impact of advance care planning on end of life care in elderly patients: randomised controlled trial. BMJ23 March 2010;340:c1345.